PENGENALAN KECERDASAN BUATAN: BAGAIMANA AI MEMPENGARUHI KEHIDUPAN MANUSIA - Ningsih, Tri Widyastuti; Zulkifli, Zulkifli; Machsunah, Yayuk Chayatun Machsunah; Ayuningtyas, Astika Ayuningtyas; Retnowati , Nurcahyani Dewi; Nugraheny, Dwi (Universitas Pahlawan Tuanku Tambusai, 2023)
Pelatihan mengenai